Coactivation: The portmanteau constructions in bilingual grammar. Issue 5 (11th May 2016) - BHATT, RAKESH M.
Abstract : Goldrick, Putnam and Schwarz (Goldrick, Putnam & Schwarz) have offered an account that must delight all linguists who have spent an inordinate amount of their professional time working on understanding the grammar of bilingual language use – just how, and why, do bilinguals produce the utterances that they do. The computational approach Goldrick et al. propose blends the grammatical principles (of the optimality kind) with general processing constraints to yield patterns of code-mixing that may be sparse – the emergence of doubled elements in bilinguals' utterances – but certainly needing an explanation. Their Gradient Symbolic Computation model is, in fact, the first robust account of the presence of doubled elements, i.e., an element of the utterance is doubled, appearing in both languages within a single utterance (see 1 below). Their account, however, does force them to make an important, but vulnerable, theoretical assumption: that grammatical principles can refer to language membership. It recalls, albeit obliquely, Belazi, Rubin and Toribio's much discussed 'Language' feature needed to mobilize their Functional Head Constraint (see Bhatt, 1997, for an empirical and theoretical critique of the Functional Head Constraint).